PENGARUH EVALUASI KREDIT DAN PENGAWASAN KREDIT TERHADAP RISIKO KREDIT MACET - Antonius Yohanes William Timuneno (Universitas Nusa Cendana, 2022)
The research background is risk of the loan credit which is the one problem which inseperable from the operations system in credit service unions in district Oebobo of Kupang City. In observation the loan default, the efforts of tackling was involved two important factors were credit evaluation and control credit. This research was conducted in 15 units of credit unions that were selected based on the criteria previously and the sample were 30 persons from credit management and supervisory elements. Technique in collecting data is observation interview, questionnnary, and documentation. The result proved that the Credit Evaluation and Credit Control had the significant partially influence to minimizing the Risk of Loan default on the credit union in district Oebobo of Kupang City through simple Linear Regression Analysis results in agreement line standard. This research also proved that the managements in credit union have to maintain and applying the evaluation and control credit system that usefull to minimize the level of loan default risk. Although it can be minimized with applying the balance credit. Keywords: Credit Control, Credit Evaluation, Risk of Loan